Smart window for kitchen with IOT system / Muhammad Adhnin Athari - Athari, Muhammad Adhnin (2023)
Nowadays, a lot of individuals choose to prepare meals at home rather than purchasing them from a store. Due to our regular use of the kitchen to prepare meals at the appropriate times, it can be claimed that its use has recently increased. They occasionally fail to tum off the stove gas. When the cooking is finished, the kitchen window is always shut. When the fan detects any gas or smoke coming from the kitchen area, it will force air to flow through the fan. Based on the amount of gas that needed to be detected in the kitchen area, the proposed method was applied in this study. The Smart Window has a sensor that are designed to detect gas or smoke in the kitchen are. If the sensors detect either of these substances, they will trigger the DC motor fan, which will force the gas or smoke to be expelled through the window. At the same time, a small bulb will change from green to red, orange to alert the user to the presence of gas or smoke. In addition to this visual warning, the system will also send a notification to the user's phone or email, alerting them to the presence of gas or smoke in the kitchen, even if they are not in physically in the house at the time. This can be especially useful if the user is away from home and unable to physically check on the kitchen themselves. Overall, this smart window system is designed to keep the user informed and safe by alerting them to the presence of potentially dangerous substances in the kitchen, and taking action to remove those substances from the room. MQ-2 will act as input while DC MOTOR, LED and Nodemcu as output.